Reposicionamento do modelo de educação corporativa no contexto da mudança organizacional: estudo de caso de uma empresa brasileira de energia - Loureiro, Juliano Mesquita (2017)
This study aimed to analyze the corporate education system of a Brazilian international energy company that undergoes a deep process of organizational change, in this paper referred as EBE S.A, aiming to identify improvable elements of its corporate university model. DESIGN/METHODOLOGY: It was adopted the case study method. The research verified if the corporate education system of EBE S.A., reflected in its corporate university, was aligned to a strategic people management model and if it was able to promote the development of the competencies that can ensure the success of EBE S.A. in its new organizational challenges. The data collection was made through documental analysis of primary and secondary sources; observation and participant observation; and semi-structured interviews with EBE S.A executives. FINDINGS: Based on the analysis and categorization of the data collected, there was a consistently critical perception regarding the corporate university with more frequent opinions favorable to its preservation since, however, in a redesigned model. The proposals indicated the expectation of changes in many aspects of the corporate university's operations. This change includes a higher approach with the company's top management, the integration of corporate education actions with the other people management processes, the strategic alignment of the competence development process, as well as structural changes in the corporate university model in order to differentiate it completely from a training and development center. PRACTICAL IMPLICATIONS: In conclusion, the process of change that the corporate university needs to pass will require resilience and innovation in an active response that promotes organizational learning. It is expected this study will contribute to other organizations in process of implementing or improving their corporate universities